The incidence function model as a tool for landscape ecological impact assessments - Graham, Laura J.; Haines-Young, Roy; Field, Richard (Elsevier, 2018)
Landscape-scale approaches to assessing the impact of land-use change on species' persistence are necessary because species depend on processes acting at varying scales, yet existing approaches to ecological impact assessment tend only to be site-based. A further major criticism of current ecological impact assessments is that they tend to be qualitative. Here we develop methods that apply the Incidence Function Model (IFM) in real urban planning contexts, by generating repeatable and comparable quantitative measures of ecological impacts. To demonstrate the methods for a case study (Nottingham, UK), we estimated landscape-scale measures of species' persistence that indicate metapopulation viability. We based these on Nottingham’s landscape when urban developments were recently proposed, then adjust the land cover to include the proposed developments, and also for two projected landscapes where 10% and 20% of the original natural or semi-natural land cover is lost. We find that the IFM shows promise as a tool for quantitative landscape-scale ecological impact assessment, depending on the size of the impact. We detected minimal differences in the species' viability measures between the original and post-development landscapes. This suggests that for small (around 2%) cumulative losses of natural/ semi-natural space, current site-based approaches are sufficient. However, when the cumulative effect of continued development was modelled by increasing the losses of natural/semi-natural land cover to 10–20% of existing cover, the impact on many of the species studied was more substantial. This indicates that a landscape-scale approach is necessary for larger, prolonged and cumulative habitat losses.